Safety Characterization and Antimicrobial Properties of Kefir-Isolated Lactobacillus kefiri - Carasi, Paula (2014)
Lactobacilli are generally regarded as safe; however, certain strains have been associated with cases of infection. Our workgroup has already assessed many functional properties of Lactobacillus kefiri, but parameters regarding safety must be studied before calling them probiotics. In this work, safety aspects and antimicrobial activity of L. kefiri strains were studied. None of the L. kefiri strains tested caused - or -hemolysis. All the strains were susceptible to tetracycline, clindamycin, streptomycin, ampicillin, erythromycin, kanamycin, and gentamicin; meanwhile, two strains were resistant to chloramphenicol. On the other hand, all L. kefiri strains were able to inhibit both Gram(+) and Gram(−) pathogens. Regarding the in vitro results, L. kefiri CIDCA 8348 was selected to perform in vivo studies. Mice treated daily with an oral dose of 108 CFU during 21 days showed no signs of pain, lethargy, dehydration, or diarrhea, and the histological studies were consistent with those findings. Moreover, no differences in proinflammatory cytokines secretion were observed between treated and control mice. No translocation of microorganisms to blood, spleen, or liver was observed. Regarding these findings, L. kefiri CIDCA 8348 is a microorganism isolated from a dairy product with a great potential as probiotic for human or animal use.